CMOS capacitance sensing device and energy harvesting for wireless sensing system using hybrid approach - Nurul Arfah binti Che Mustapha (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Sensor measurement using capacitive sensor has gain popularity in many applications over other resistive sensor and inductive sensor. The method of converting stimuli input to a readable detection output voltage can be divided into many broad methods, such as capacitive-to-digital converter (CDC), capacitive-to-frequency converter (CFC) and capacitive-to-voltage converter (CVC). One of the methods in CVC is known as differential CVC. It is known to be a very symmetrical in design, sensitive to detection, accurate and easy to be implemented using discrete components. Previous research to date has shown the range of frequency operation using discrete component is only up to 10 kHz, very low detection range and has only implemented the differential CVC circuit solely using normal power supply or battery dependent. Hence, the objective of this work is to design and evaluate the performance of the differential capacitive sensing, while integrating multiple sources from different harvesters as its power source. Electrical characterization of the device performance is also studied in this research. The proposed differential CVC circuit requires only one single supply from the energy harvester implemented by using hybrid technique and was realised by the discrete components. Results has shown a wide detection range of 2 – 23 pF, and the best is recorded at 200 kHz frequency, with output voltage of 1.5 – 2.22 V. This is realised by implementing 3.3 V power supply, with nominal detection capacitor Cx0 = 5 pF. Circuit has consumed 3.83 mW of power, which is 28.9 % improvement from the previous result. Both with and without parasitic, the proposed circuit has shown high level of linearity of R-squared value of up to 0.99944 using 0.1 pF capacitance change with sensitivity of 0.05431 mV per fF change, across 40 kHz to 400 kHz frequency. Sensitivity has been improved by 43 % from the previous work. Comparison of the experiment work with the theory has shown 5% error in difference. The proposed differential CVC is also suitable to be used as a sensor node in area that limit access to human for battery replacement and it is suitable to integrate pressure and accelerometer sensor to the system.